FOREIGN INVESTMENT IN TRANSITION ECONOMIES: THE ROLE OF INFORMATION - Andrä, Jan; Broll, Udo (Journal of European Economy, 2017)
This paper examines the importance of economic incentives as a determinant of foreign direct investment in transition economies. We argue that an international public-private joint venture can be seen as an institution that makes the disincentive problem less severe in newly liberalized economies. By a publicprivate joint venture we describe a set up where a foreign firm decides on the volume of foreign investment and the host country government offers a package of start-up investment and investment sharing rules to mitigate distortions which typical arise in economies in transition and lower developed countries. The public-private joint venture may take on a variety of forms to cope with different kind of distortions and economic risk.